Efficiency of Using Glutamine as a Component of Parenteral Nutrition in Neonates with Sepsis - D. V. Petrov; S. V. Bobovnik; E. N. Kamenskaya; E. A. Shcherbakova (Общая реаниматология, 2011)
The incidence of acute destructive pancreatitis is steadily increasing in the past decade. Objective: to emphasize the high efficiency of complex efferent therapy in treating patients with infectious pancreonecrosis. Subjects and methods. The authors compared 2 similar groups of patients with disseminated infectious pancreonecrosis. Group 1 was on the basic intensive therapy (a control group) and Group 2 received a set of efferent methods, including an original procedure combining membrane plasmapheresis and sodium hypochlorite, in addition to the standard intensive therapy (a study group). Results. There were reductions in intensive care unit bed-days and in the number of fatal outcomes. Conclusion. The set of efferent methods has shown to be effective in treating patients with this pathology. Key words: infectious pancreonecrosis, efferent therapy methods, hemodiafiltration, plasmapheresis, sodium hypochlorite.